Colonialism, genocide and International Relations: the Namibian–German case and struggles for restorative relations. (September 2020) - Weber, Heloise; Weber, Martin
The case of the first genocide of the 20th century, committed by German colonial troops against Ovaherero and Nama peoples in what is today Namibia, poses a significant ethical and political challenge not only in practice but also for International Relations theory and theorising. We develop our critical analysis by building on postcolonial critiques of eurocentrism in IR and world politics, and on critical historiographies of the discipline. In particular, we show how the bedrock of dominant international institutional arrangements in the early 20th century rests on a normative inversion, which can be explicated clearly in the context of the Ovaherero and Nama experiences. The normative inversion is manifested in the claims to supreme moral authority for continued European colonial rule in the aftermath of genocidal violence. While the League of Nations (LoN), and the legacies of imperialism have increasingly been addressed in historiographies of IR, neither this normative inversion, nor its political implications have been explicated in the way we pursue this here. Through the lens of our case, we argue that how IR and IR theory conventionally conceive of the international political order is not plausible or justifiable in light of the normative inversion. The struggles for justice and restorative relations by Ovaherero and Nama peoples draw attention to necessary shifts in political practices. The case signals the need for a more fundamental rethinking of premises in international political theory, and of global public political history. This can be meaningfully addressed by acknowledging and explicitly processing the implications of the normative inversion, its antecedent conditions, and its continuing presence in world ordering.